Endothelial cells exposed to phosphate and indoxyl sulphate promote vascular calcification through interleukin-8 secretion. Issue 7 (27th November 2018) - Bouabdallah, Jeanne; Zibara, Kazem; Issa, Hawraa; Lenglet, Gaëlle; Kchour, Ghada; Caus, Thierry; Six, Isabelle; Choukroun, Gabriel; Kamel, Saïd; Bennis, Youssef
Abstract: Background: Vascular calcification (VC) is amplified during chronic kidney disease, partly due to uraemic toxins such as inorganic phosphate (Pi) and indoxyl sulphate (IS) that trigger osteogenic differentiation of vascular smooth muscle cells (VSMCs). These toxins also alter endothelial cell (EC) functions but whether this contributes to VC is unknown. Here, we hypothesized that ECs exposed to Pi and IS promote VSMC calcification. Methods: Human umbilical vein ECs were treated with Pi, IS or both, and then the conditioned media [endothelial cell conditioned medium (EC-CM)] was collected. Human aortic SMCs (HASMCs) were exposed to the same toxins, with or without EC-CM, and then calcification and osteogenic differentiation were evaluated. Procalcifying factors secreted from ECs in response to Pi and IS were screened. Rat aortic rings were isolated to assess Pi+IS-induced calcification at the tissue level. Results: Pi and Pi+IS induced HASMCs calcification, which was significantly exacerbated by EC-CM. Pi+IS induced the expression and secretion of interleukin-8 (IL-8) from ECs. While IL-8 treatment of HASMCs stimulated the Pi+IS-induced calcification in a concentration-dependent manner, IL-8 neutralizing antibody, IL-8 receptors antagonist or silencing IL-8 gene expression in ECs before collecting EC-CM significantly prevented the EC-CM procalcifying effect. IL-8 did not promote the Pi+IS-induced osteogenic differentiation of HASMCs but prevented the induction of osteopontin (OPN), a potent calcification inhibitor. In rat aortic rings, IS also promoted Pi-induced calcification and stimulated the expression of IL-8 homologues. Interestingly, in the Pi+IS condition, IL-8 receptor antagonist lifted the inhibition of OPN expression and partially prevented aortic calcification. Conclusion: These results highlight a novel role of IL-8, whose contribution to VC in the uraemic state results at least from interaction between ECs and VSMCs.